2017
DOI: 10.1002/ijc.31165
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of glucose transporters in prostate cancer: Are they a new feature to characterize carcinomas?

Abstract: One of the hallmarks of cancer cells is the increased ability to acquire nutrients, particularly glucose and glutamine. Proliferating cells need precursors for cell growth and NADPH reducing equivalents for survival. The principal responsible for glucose uptake is facilitative glucose transporters (GLUTs), which usually are overexpressed in cancer cells. Besides their role in glucose uptake, GLUT transporters are able to transport other compounds such as dehydroascorbic acid or uric acid. They play a major rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 119 publications
(218 reference statements)
1
52
0
Order By: Relevance
“…In prostate cancer (PCa), glucose metabolism plays a major role in progression [14] . Androgens can activate the metabolic regulator AMP-activated kinase (AMPK), promoting oxidative phosphorylation (OXPHOS) [15] .…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer (PCa), glucose metabolism plays a major role in progression [14] . Androgens can activate the metabolic regulator AMP-activated kinase (AMPK), promoting oxidative phosphorylation (OXPHOS) [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, cancer cells show a high expression of glucose transporters GLUT1 and GLUT3 due to the metabolic changes and high demands of energy through neoplastic transformation [43,55,56]. In IDH1 +/+ and IDH1 R132H/+ cells, GLUT1 and GLUT3 levels were reduced upon treatment with VC.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxia or nutrient deprivation, tumor cells overexpress at least one of the GLUT transporters, predominantly GLUT1. A high expression of this glucose transporter has been described in many types of cancer including cervical cancer [ 65 , 66 ]. It has been reported that GLUT1 is a transcriptional target of HIF1, which activates a panel of target genes for example GLUT-1, GLUT-3, carbonic anhydrase IX (CAIX), and vascular endothelial growth factor (VEGF), promoting the transcription of glycolytic enzymes [ 58 , 66 , 67 ].…”
Section: Hpv Oncoproteins and Cellular Metabolismmentioning
confidence: 99%
“…A high expression of this glucose transporter has been described in many types of cancer including cervical cancer [ 65 , 66 ]. It has been reported that GLUT1 is a transcriptional target of HIF1, which activates a panel of target genes for example GLUT-1, GLUT-3, carbonic anhydrase IX (CAIX), and vascular endothelial growth factor (VEGF), promoting the transcription of glycolytic enzymes [ 58 , 66 , 67 ]. Cancer cells have a high demand of nutrients due to their high rate of proliferation, so the entry of glucose by facilitated diffusion through GLUT transporters could be insufficient, being required other mechanisms of glucose uptake may be required.…”
Section: Hpv Oncoproteins and Cellular Metabolismmentioning
confidence: 99%
See 1 more Smart Citation